Feed- and feed additives-related aspects of gut health and development in weanling pigs - Pluske, John R (BioMed Central, 2013)
The development of new/different management and feeding strategies to stimulate gut development and health in newly-weaned pigs, in order to improve growth performance while minimizing the use of antimicrobial compounds such as antibiotic growth promotants (AGP) and heavy mineral compounds, is essential for the long-term sustainability of the pig industry. Factors including the sub-optimal intake of nutrients and energy, inappropriate microbiota biomass and (or) balance, immature and compromised immune function, and psychosomatic factors caused by weaning can compromise both the efficiency of digestion and absorption and intestinal barrier function through mucosal damage and alteration of tight junction integrity. As a consequence, pigs at weaning are highly susceptible to pathogenic enteric conditions such as post-weaning diarrhea that may be caused by serotypes of enterotoxigenic Escherichia coli. Many dietary components, e.g., protein, fiber, feed additives and minerals, are known to influence microbial growth in the gastrointestinal tract that in turn can impact upon pig growth and health, although the relationships between these are sometimes not necessarily apparent or obvious. In a world climate of increased scrutiny over the use of antibiotics per se in pig production, certain feed additives are seen as alternatives/replacements to antibiotics, and have evolved in some cases to have important roles in everyday commercial pig nutrition. Nevertheless and in general, there remains inconsistency and variability in the efficacy of some feed additives and in cases of severe disease outbreaks, for example, therapeutic antibiotics and/or heavy minerals such as zinc oxide (ZnO) are generally relied upon. If feed ingredients and (or) feed additives are to be used with greater regularity and reliability, then it is necessary to better understand the mechanisms whereby antibiotics and minerals such as ZnO influence animal physiology, in conjunction with the use of appropriate challenge models and in vitro and in vivo techniques.